MAPEAMENTO COMO ESTRATÉGIA DE COMUNICAÇÃO NA GESTÃO PARTICIPATIVA DE RECURSOS HÍDRICOS - Santos, Analaura Vieira (2022)
In Brazil, the management of water resources is regulated by Law No. 9,433, of January 8, 1997, based on decentralized, integrated and participatory management. Among the institutional bodies belonging to the Water Resources Management System, the basin committees are collegiate bodies of a participatory nature, composed of users, organized civil society and public authorities (Federal, State and Municipal). The involvement and mobilization of society are challenges in the decision-making process of the committees. Given these premises, this work emphasizes the use of mapping as a participatory methodology to expand interaction and communication, taking the Guandu River Hydrographic Basin Committee as a parameter for analysis and proposals. We use qualitative and descriptive methodology, a bibliographical and documentary research being carried out. We analyzed the means of communication used in the preparation of the water resources plan and the proposal for the framing of water bodies, we identified that these means serve to obtain information from the community, but they become a one-way street, not allowing interaction and power of decision. By analyzing the potential and limits of participatory mapping, we hope to contribute to the elaboration of the diagnosis and the prognosis of the framework, aiming at an effective participation of the committee's representatives and those they represent. but they become a one-way street, not allowing interaction and decision-making power. By analyzing the potential and limits of participatory mapping, we hope to contribute to the elaboration of the diagnosis and the prognosis of the framework, aiming at an effective participation of the committee's representatives and those they represent. but they become a one-way street, not allowing interaction and decision-making power. With the analysis of the potential and limits of participatory mapping, we hope to contribute to the elaboration of the diagnosis and the prognosis of the framework, aiming at an effective participation of the committee's representatives and those they represent.